THE EFFECT OF AUDIT OPINION, CHANGE OF MANAGEMENT, FINANCIAL DISTRESS AND SIZE OF A PUBLIC ACCOUNTING FIRM ON AUDITOR SWITCHING - Irma Ade Alisa; Intan Ayu Rosita Devi; Fradini Brillyandra (Jurnal Akuntansi Trisakti, 2019)
This research aims to analyze and determine the effect of the audit opinion, change of management, financial distress, and the size of the public accounting firm on the auditor switching. This research uses secondary data from the official website of the Indonesia Stock Exchange. This research was conducted on manufacturing companies that have been listed in the Indonesia Stock Exchange from 2015-2017. The population in this research were all manufacturing companies. This research uses the purposive sampling method. Samples were 94 companies of 144 companies listed on the Indonesia Stock Exchange in 2015-2017, so the research data analyzed amounted to 282. The analysis technique in this research was the logistic regression analysis. The results of hypothesis testing in this research indicate that audit opinion, Change of Management, and size of public accounting firm have a positive effect on auditor switching. Meanwhile, financial distress does not affect auditor switching.